Technology Acceptance Model: Determinans Actual System Use Of E-Bupot Unification Applications - Nabila Rif'atul Izzah; Dyah Febriantina Istiqomah (Jurnal Akademi Akuntansi, 2023)
The research aimed to examine the influence of perceptions, attitudes, and intentions in using the e-Bupot Unification application with the Technology Acceptance Model approach. Survey with the object of Corporate Taxpayers using e-Bupot Unification registered at Jakarta Kebayoran Lama Primary Tax Service Office (KPP) by measuring constructs of perceived ease of use, perceived usefulness, attitudes toward use, behavioral intentions, and actual system use, using a questionnaire instrument to collect primary data on a sample of 110 Corporate Taxpayers. This research analyzed data and hypotheses using the Partial Least Square (PLS) method and SmartPLS 3.0 software. The analysis results show that “Perceived Ease of Use” positively and significantly affects “Perceived Usefulness” and “Attitudes Toward Use”. “Perceived Usefulness” positively and significantly affects “Attitudes Toward Use” and “Behavioral Intentions”. "Attitude towards Use" significantly influences "Behavioral Intention." "Behavioral Intention" significantly influences "Actual System Use."